Enabling the Future Auto with Model-Driven Services - Helander, Johannes; Veanes, Margus (National Workshop on High-Confidence Automotive Cyber-Physical Systems., 2008)
Building systems out of models may be a good approach for better understanding and specifying the behavior of software and its interaction with the physical world. This paper proposes taking the models beyond specification and validation, making models an integral part of any cyber-physical system. Continuous and discrete models can be used to predict and adapt to situations and to build reliable distributed computing systems. Models describing behavior and features of an automobile can be used to dynamically configure an automobile, making a subscription model of features possible.